Definição do ponto de referência endoscópico nasal ao acesso cirúrgico à base anterior do crânio por estudo anatômico de cadáveres - Andressa Vinha Zanuncio (2011)
Operation guided by endoscopic nasal endoscope is used to treat diseases of the paranasal sinuses, nasal cavity and skull base. Detailed knowledge of nasal anatomy is important to achieve a safe and efficient operation, minimizing risks and complications. This study aims to measure the distances of the posterior wall of the right and left maxillary sinuses to the anterior cranial base and to compare them with genus, height, weight, age and ethnicity of the cadavers. Detailing a new anatomical landmark to perform safer operations of the paranasal sinuses and of the anterior skull base can set references for other endoscopic surgical access. The cadavers were necropsied at the Death Verification Service of the University of São Paulo (SVO-USP), São Paulo in July 2010. Nine measures of the paranasal sinuses of the left and right sides in relation to the anterior cranial base of 60 cadavers with minimum age of 17 years were performed and recorded on data sheets according to genus, height, weight, age and ethnicity. The opening of the medial wall of the maxillary sinus was performed with complete dissection of the anterior and posterior ethmoid and sphenoid sinuses, for measurements. Measures of higher, middle and inferior points of the posterior wall of the maxillary sinus to the 90-degree angle (the point where deflection of the skull base starts to form the anterior wall of the sphenoid); higher, middle and inferior points of the posterior wall of the maxillary sinus to the nasal spine; recess of the frontal sinus to the nasal spine; recess of the frontal sinus to the angle of 90º and angle of 90º to the anterior nasal spine were performed. Only the first three measures were used because they did not vary in relation to genus, height, weight, age and ethnicity or in relation to right and left sides. Values of these measures were always higher than 1.5 cm in the cadavers. Association between BMI, ethnicity, genus, age, height and weight of the bodies on the measures assessed was not observed. Association between the measure of 90 ° to the superior, middle and lower part of the posterior jaw as the categorical and quantitative traits was not observed. There is a fixed minimum distance between the posterior superior wall of the sinus and 90 degrees angle, with more than 1.5 cm, which can facilitate a safe opening of the paranasal sinuses during endoscopic nasal operations.